The effects of observability and an information nudge on food choice - Astrid Dannenberg; Eva Weingärtner (Philipps-University Marburg, School of Business and Economics, 2023)
Our choice of food has major impacts on the environment. At the same time, it is visible to all people with whom we spend our daily lives. This raises the question of whether people are adapting their diets to gain a green reputation, as has been observed for other environmentally relevant consumption choices. Using an experiment in which participants can choose between vegan, vegetarian, and meat-based food vouchers, we examine how observation by others and the provision of an information nudge influence food choices. The results show that providing an information nudge reduces the likelihood of choosing meat by 12 percentage points. Observation by others does not significantly reduce the likelihood of choosing meat. Contrary to our prediction, when participants are observed and receive the information nudge, they are less inclined to choose one of the more sustainable options. We discuss the reasons for the partly surprising results and the implications for policy.
Keywords: C9; D91; Q18; 330; Food choice; meat consumption; information nudge; observability; experiment